(untitled) (Cadernos de Sociomuseologia, 2022)
The article deals with the permanence in most museums in Portugal, of an ideology that expressed the colonial relationship of the past and which, in essence, remains in force in Portuguese society. This ideology in its current form, which was constructed after the Berlin Conference (1895) by a not very large group of academics, military and political elites, who, in particular during the Estado Novo period, saw their visions of the colonial relationship enshrined in the colonial policy of António Salazar and Marcelo Caetano. The examples given on the different approaches to the nature of the colonial relationship in the 20th century clearly show that the thinking of late 19th and 20th century ideologues, including the times of the last liberation war, evolved from unfettered pragmatism to giving gives rise to an ideology that seeks to present a colonial relationship based on mutual respect, affection, human solidarity, in short, on "Christian communion". The dominant ideology continues to justify colonization, war (colonial or liberation), forced labor, the distinction between the principles of a more advanced culture and superior morality. All in the name of an imagined colonial relationship respectful of human rights. The article analyzes some manifestations of this ideology at the Museu da Guerra Colonial in Famalicão that, in a way, can illustrate how, under the cover of an allegedly “neutral” discourse, the values of coloniality are maintained. The article draws attention to the need to take into account recent UNESCO documents or the new definition of Museum approved by ICOM in 2022, which could greatly help museums to act more in accordance with Human Rights Keywords: Museums, coloniality, colonial ideology